LEARNING CELL TECHNIQUE TOWARD READING COMPREHENSION OF NARRATIVE TEXT - Rakhmawati, Dian (JURNAL SMART, 2015)
AbstractÂ The purposes of this study are to identify the differences of reading comprehension in control and experimental group of senior high school students and to find out the effectiveness of Learning Cell as the technique in teaching reading comprehension of narrative text.The quantitative method was conducted in this study and the researcher used Nonequivalent Control Group Design which the observation is done twice, before and after treatment. The subject of this research was two groups, which consist of 34 students in each group.Then reading comprehension test was used as research instrument. The result of the t-test computation showed that tobserved was higher than t table (6.184>2.036), with the degree of freedom 32 and the level of significance 0.05 and the probability (Asymp.Sig.2 tailed) was lower than the level of significance (0.000<0.05). It can be concluded that the null hypothesis of no difference was rejected. In other words, teaching reading comprehension by using learning cell technique is effective than teaching reading comprehension by using conventional way.Â Keywords: Learning cell, reading comprehension, narrative textÂ